Isolation and identification of biosurfactant producing bacteria from wastewater treatment pool of Bumi Siak Pusako – Pertamina Hulu Ltd, Siak - Sri Ayu Elsi Maita; Hasbi Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Biosurfactants are surfactant compounds produced by microorganisms and it has capability to reduce surface tension of water. To understand the types of biosurfactant producing bacteria,a research has been conducted in March 2018. Samples were taken with glass bottles at 6 sampling points in the wastewater treatment pool of Bumi Siak Pusako – Pertamina Hulu, Ltd and stored on the refrigerator at 4oC.  The  samples were serially diluted and enriched with BHI (Brain Heart Infusion) media for 24 hours. Then  this bacteria was identified biochemically and using a 16 sr RNA method. Results shown that the number of colonies obtained was 3.1 x 106 cfu/ml. After the emulsification test, 3 isolates were able to produce foam, they were Klebsiella sp, Citrobacter sp and Aeromonas sp. Keywords : surface tension, Klebsiella sp, Citrobacter sp, Aeromonas sp, 16 sr RNA, emulsification